2017
DOI: 10.1002/ijc.30788
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in miR‐1262 regulatory region confers the risk of lung cancer in Chinese population

Abstract: It has been proposed that the majority of disease-associated loci identified by genome-wide association studies (GWAS) are enriched in non-coding regions, such as the promoter, enhancer or non-coding RNA genes. Thus, we performed a two-stage case-control study to systematically evaluate the association of genetic variants in miRNA regulatory regions (promoter and enhancer) with lung cancer risk in 7,763 subjects (discovery stage: 2,331 cases and 3,077 controls; validation stage: 1,065 cases and 1,290 controls)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…In addition, in the results of an expanded study on lower grade glioma, more statistically significant genes were found. There were reports with findings consistent with those of ours on hsa-miR-1262, hsa-miR-455-3p, LPAL2 [83][84][85][86], and some reports even contradicted our findings on hsa-miR-204-5p and hsa-miR-197-3p [87,88]. Although related studies are still insufficient, the previous report about hsa-miR-186-5p in glioblastoma contradicted our findings [89].…”
Section: Discussionsupporting
confidence: 64%
“…In addition, in the results of an expanded study on lower grade glioma, more statistically significant genes were found. There were reports with findings consistent with those of ours on hsa-miR-1262, hsa-miR-455-3p, LPAL2 [83][84][85][86], and some reports even contradicted our findings on hsa-miR-204-5p and hsa-miR-197-3p [87,88]. Although related studies are still insufficient, the previous report about hsa-miR-186-5p in glioblastoma contradicted our findings [89].…”
Section: Discussionsupporting
confidence: 64%
“…Evidence has shown that miRNAs are involved in the initiation and development of various types of cancers, and these molecules function as anti-oncogenes or oncogenes. SNPs in miRNAs, including primary, precursor and mature miRNA, may change the expression level and alter the binding affinity of miRNAs, and further regulate the expression of the target genes, thereby markedly impacting cell pathway regulation, which defines cellular fates [ 19 , 20 ]. In the present study, we observed that rs11134527 in pri-miR-218-2 and rs531564 in pri-miR-124-1 were associated with CIN and cervical cancer in a Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more studies about the association between SNPs and lung cancer risk were conducted. The studies of Chen D [ 18 ], Xie K [ 19 ], Yin Z [ 20 ] et al all came to a significant conclusion. SNPs play an important role in the occurrence, development and prognosis of lung cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%